Development of a Simple Business Website for Young Entrepreneurs Using Bootstrap - Vizayaksa, Gema; Raisya, Alika; Muhammad Hably Nasrullah; Ilham, Muhammad Arifin; Akwa, Villian Shah; Hendra; Adharani, Yana; Mujiastuti, Rully; Rosanti, Nurvelly (Edumedia Solution, 2026)
The utilization of digital technology has become essential in business development. However, many young entrepreneurs, students, and members of the general public still face difficulties in developing professional business websites due to limited technical knowledge and lack of structured guidance. This community service program aimed to enhance participants’ digital literacy and practical skills in developing responsive business websites using the Bootstrap framework. The program applied an educative and participatory method through online webinars and hands-on workshops. Webinar sessions delivered conceptual materials on business websites, web development fundamentals, responsive design, and Bootstrap introduction, while workshop sessions provided direct guidance for building website structures and implementing Bootstrap components. Program effectiveness was measured using pretest, posttest, and participant feedback. The pretest results showed an average score of 79.5 with varied initial understanding. After the program, the posttest average increased to 92.32, with most participants achieving high scores. Participant feedback also indicated high satisfaction with material relevance, instructor competence, and online service quality. These results demonstrate that the combination of webinars and workshops effectively improves participants’ knowledge, digital literacy, and ability to independently develop Bootstrap-based business websites.